Analisis Portofolio Optimal Menggunakan Metode Multi Objektif pada Saham Jakarta Islamic Index - Efriandi Dwi Septyanto; Media Rosha (UNIVERSITAS NEGERI PADANG, 2019)
Abstract- Multi-Objective method for portfolio is a portfolio that is aimed to minimize the risks and maximize the expected return at the same time.The multi-objective optimization can be solved with scalarization which is a standard technique to find the optimum points for each optimization vector problems.The purpose of the research is to find out how to build optimal portfolios with optimization method of Multi-Objective and to know the proportion of their respective shares of the selected Jakarta Islamic Index in the optimal portfolio. The steps were taking the data of the stock prices of the companies that have been selected, calculating the expected return and variance-covariance of the return for each stocks, calculating the value of the portfolio of each stocks, and calculating the value of expected return of a portfolio that is formed using the method of Multi objective. The research results obtained optimal portfolios which was measured using coefficient k=10 with the capital sharing that was invested stock to ASII, CPIN,CTRA, EXCL, ICBP, PTBA, SMGR, and TLKM with proportion stock are 18,61%, 29,60%, 0,30%, 0,44% , 28,70%, 6,91%, 7,92%, dan 7,52%. Keywords: Multi Objective Methods, shares of JII, Optimal Portfolio